The Counseling Experiences of Transgender and Gender Nonconforming Clients. (15th September 2017) - McCullough, Rafe; Dispenza, Franco; Parker, Lindy K.; Viehl, Cory J.; Chang, Catharina Y.; Murphy, Thomas M.
Abstract : The counseling experiences of 13 transgender and gender nonconforming (TGNC) individuals were examined via semistructured, in‐depth interviews. Using multiple standards of trustworthiness (e.g., member checking, negative case analysis), the authors analyzed each interview from an interpretative phenomenological analytic framework. Four main themes were identified: mental health professional selection process, transaffirmative approach, transnegative approach, and support systems beyond counseling. Implications for implementing culturally responsive TGNC affirmative counseling, TGNC sensitive counselor training, and social justice–oriented research are discussed.